Decline in pulmonary function during chronic hepatitis C virus therapy with modified interferon alfa and ribavirin. Issue 4 (14th February 2013) - Foster, G. R.; Zeuzem, S.; Pianko, S.; Sarin, S. K.; Piratvisuth, T.; Shah, S.; Andreone, P.; Sood, A.; Chuang, W.‐L.; Lee, C.‐M.; George, J.; Gould, M.; et al.
Summary: Rare interstitial lung disease cases have been reported with albinterferon alfa‐2b (albIFN) and pegylated interferon alfa‐2a (Peg‐IFNα‐2a) in chronic hepatitis C virus (HCV) patients. Systematic pulmonary function evaluation was conducted in a study of albIFN q4wk vs Peg‐IFNα‐2a qwk in patients with chronic HCV genotypes 2/3. Three hundred and ninety‐one patients were randomly assigned 4:4:4:3 to one of four, open‐label, 24‐week treatment groups including oral ribavirin 800 mg/d: albIFN 900/1200/1500 μg q4wk or Peg‐IFNα‐2a 180 μg qwk. Standardized spirometry and diffusing capacity of the lung for carbon monoxide (DLCO) were recorded at baseline, weeks 12 and 24, and 6 months posttreatment, and chest X‐rays (CXRs) at baseline and week 24. Baseline spirometry and DLCO were abnormal in 35 (13%) and 98 (26%) patients, respectively. Baseline interstitial CXR findings were rare (4 [1%]). During the study, clinically relevant DLCO declines (≥15%) were observed in 173 patients (48%), and were more frequent with Peg‐IFNα‐2a and albIFN 1500 μg; 24 weeks posttreatment, 57 patients (18%) still had significantly decreased DLCO, with a pattern for greater rates with albIFN vs Peg‐IFNα‐2a. One patient developed new interstitial CXR abnormalities, but there were no clinically relevant interstitial lung disease cases. The risk of persistent posttreatment DLCO decrease was not related to smoking, alcohol, HCV genotype, sustained virologic response, or baseline viral load or spirometry. Clinically relevant DLCO declines occurred frequently in chronic HCV patients receiving IFNα/ribavirin therapy and commonly persisted for ≥6 months posttherapy. The underlying mechanism and clinical implications for long‐term pulmonary function impairment warrant further research.